A new troglobitic species of Allochthonius (subgenus Urochthonius) (Pseudoscorpiones, Pseudotyrannochthoniidae) from Japan - Ana Clara Moreira Viana; Rodrigo Lopes Ferreira (Subterranean Biology, 2021)
Allochthonius (Urochthonius) yoshizawai sp. nov., found in Hiura-do Cave, a limestone cave located in the municipality of Kumakogen, Ehime Prefecture, Japan, is described. It can be distinguished from the consubgeneric species mainly by the carapacal chaetotaxy (6–2, 18), by the presence of 6 setae on the cheliceral palm, by the rallum with 11 blades, by the presence of 8 clavate coxal blades on coxae I, and by the decreased number and distinct shape of the chelal teeth. A redescription of the subgenus Urochthonius, and keys to the subgenera of Allochthonius and to the species and subspecies of Urochthonius are also provided, as well as some ecological remarks, a brief discussion on troglomorphisms for the subgenus, and potential threats for this species.